Protein-Energy Intake, Sleep Quality and Quality of Life Before and After Bariatric Surgery: The Malaysian Context - Poh Yue, Tsen; Gee, Tikfu; Awang, Raflis Ruzairee; Mohd Yusof, Barakatun Nisak Binti; Shu Yu, Lim; Leng, Ang Yeu; Jia Ying, Soo; Wei, Lee Yu (International Journal of Innovative Research in Medical Science, 2019)
Background: This prospective observational study aimed to determine the impact of bariatric surgery on the protein-energy intake, sleep quality and quality of life (QOL) of bariatric surgery patients in Malaysia. Methods: The study evaluated 52 morbidly obese patients who underwent bariatric surgery. The short version of the World Health Organization Quality of Life questionnaire (WHOQOL-BREF), Epworth Sleepiness Scale (ESS) questionnaire and three days 24-hour diet recall were used to evaluate the health-related QOL, sleep quality and protein-energy intake of patients. Patients were interviewed before and 3 months after surgery. Results: The mean age was 42 years and 69.2% of them were female. The mean BMI was 42 kg/m2. Patients with morbid obese had significantly lowered QOL scores, mean intake of 1898 kilocalories and 75 g protein per day before the surgery. The reduction of weight after bariatric surgery showed an increase in QOL score in all areas (P < 0.05) and a decrease on ESS score from 6.3 ± 4.0 to 2.9 ± 2.3 (p < 0.00). The mean intake 3 months after surgery was 718 kilocalories, 39g protein per day. Conclusion: Bariatric surgery is proven effective in achieving significant weight loss, improving sleep quality and QOL among Malaysian obese patients within 3 months of surgery. However, the newly restricted stomach after bariatric surgery significantly reduces food intake in the first 3 months. Therefore, a more careful follow-up with patients is required.